Faktor-Faktor yang Berpengaruh terhadap Kelelahan Kerja pada Petugas Pemadam Kebakaran : Tinjauan Pustaka - Adhim, Muhammad Risqi; Mayasari, Diana; Setiawan, Gigih (CV. Jasa Sukses Abadi, 2024)
Occupational Safety and Health (K3) is an important aspect in protecting workers from the risk of work accidents, including work fatigue which can have an impact on physical and mental health. Workplace fatigue often occurs due to various factors that can cause physiological and psychological disorders. Firefighters are a profession that has a high risk of work fatigue, considering the high number of fire incidents and the response system which is still not optimal. Heavy workloads and high physical and mental demands further increase the risk of work fatigue in firefighters. This research uses a literature review method by analyzing various academic journals published in the last five years (2019–2024). The research results show that there are two main factors that influence work fatigue, namely internal factors and external factors. Internal factors include age, years of service, smoking status, and sleep patterns. Meanwhile, external factors include workload, work stress, work attitudes and working time. Untreated work fatigue can have a negative impact on the work safety and productivity of firefighters, and even increase the risk of work accidents. Therefore, preventive efforts and a thorough evaluation of work safety limits are needed to minimize the risk of fatigue and create a safer and healthier work environment for firefighters.